Tuning of agent-based computing - Byrski, Aleksander (Computer Science, 2013)
In this paper an Evolutionary Multi-agent system based computing processis subjected to detailed analysis of the parameters in order to ground a basefor better understanding this meta-heuristics from the practitioner’s point of view.After reviewing the concepts of EMAS and its immunological variant, a series of experiments is shown and theresults of influencing of search outcomes by certain parameters are discussed.